Evaluation on the thermal performance of external insulation system in apartment building remodelling. (May 2015) - Cho, S. H.; Lee, H. Y.; Kang, J. S.; Lee, Y. J.; Choi, G. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Thermal insulation plays a significant role in increasing building energy saving and creating comfortable indoor environment by reduction of heat transfer between indoor and outdoor environments. This study aims to investigate the insulation performance of the external insulation system applied in remodelling apartment buildings using the equivalent U-value. The results of this study indicate that thermal performance achieved by the external insulation system was improved and panel approach system is more excellent than flame-retardant polyurethane foam. The results of this study indicate that the external insulation system was investigated in this study, and the result confirms that the application of the external insulation system in remodelling apartment buildings will contribute to energy conservation. The above-mentioned results imply that external insulation system applied in remodelling apartment buildings can significantly contribute to the improvement in energy-efficient of buildings.